Regional Hyperthermia Combined with Chemotherapy in Advanced Gastric Cancer - Fang, Hongming (Open Med (Wars), 2019)
INTRODUCTION: This study aims to investigate the potential effects of regional hyperthermia combined with chemotherapy (RHCT) as a treatment strategy for advanced gastric cancer (AGC). METHOD: 118 AGC patients were randomly divided into treatment plans with chemotherapy (CT) alone or with RHCT. The prognostic value of clinicopathologic characteristics was assessed in terms of overall survival of AGC patients. RESULTS: The disease control rate was determined to be 70.9% and 46.0% for the RHCT and CT group, respectively (P = 0.006). The median survival was determined to be 23.5 months for the RHCT group and 14.0 months for the CT group (P = 0.010). The 3-year survival rate for the RHCT group was 11.4% and 0% for the CT group (P = 0.018). No difference in grade 3 or 4 adverse events was observed between the two groups (P > 0.05). Multivariate analysis showed that hyperthermia, disease stage, Glasgow prognostic score, and abdominal metastasis were closely associated with the prognosis of these AGC patients. CONCLUSION: The study suggests that combination treatment with RHCT for AGC has clinical potential for both short- and long-term curative effects without compromising toxicity.